Evidence‐based classification in golf for athletes with a vision impairment: A Delphi study. (21st September 2022) - Hynes, Niall J.; Beukes, Eldre W.; Hawkes, Roger; Bennett, Howard A.; Hamilton, Christian; Jayabalan, Prakash; Allen, Peter M.
Abstract: Vision‐impaired (VI) golf is a global para‐sport currently played under several different classification systems under different bodies. This study aimed to gather expert opinion to determine whether the current classification systems are fit for the purpose intended and to identify any particular issues where VI impacts the game of golf for the disabled (G4D). A panel of 20 participants with expertise in G4D took part in a three‐round Delphi study. The panel agreed that the current classification system(s) for VI golf did not or only partially fulfilled the aim to minimise the impact of VI on the outcome of competition and that there should be one, internationally recognised, classification system. It was agreed that other metrics of VI, in addition to the measurement of visual acuity (VA), need to be considered. Intentional misrepresentation of VI was identified as a cause for concern. The panel agreed that the current classification system does not fully achieve its purpose. Any changes that are made to these classification systems need to be evidence based specific to VI golf. Further research is required to determine how measures of VI affect golfing performance and whether other metrics other than VA are required.